The Practice of Village Governance: Comparing traditional form of Desa and Cultural Form of Nagari - Muhammad Muhammad (Publica: Jurnal Pemikiran Administrasi Negara, 2021)
Indonesia has been implementing a more in-depth decentralization system encouraging village governance since 2014. Since then, village governments have been given more autonomy on governing village funds to promote village development further. This paper aims to compare two forms of the Village (desa and nagari) in terms of the practice of village governance. This study mainly uses a qualitative descriptive method to compare the implementation of village governance in both traditional form (desa) and cultural form (nagari). With further Lowndes and Sullivan’s analytical framework of neighbourhood governance, this study suggests all types of neighbourhood governance have been practiced in both forms. Although village government type is more significant in both forms, the social rationale is more significant in nagari because of the cultural aspect. Finally, based on the comparison of both forms of Village, this paper advocates some implications in the implementation of village governance.